Variabilidade espacial da qualidade fisiológica de sementes de soja estimada pela condutividade elétrica massal e individual - Mattioni, Nilson Matheus (2013)
Many factors can affect soybean seeds physiological quality in the field, and these factors do not occur in a homogeneous form. The aim of this study was to determine the spatial variability of soybean seed quality in a production fields during the pre-harvest by massal and individual electrical conductivity. Seeds were harvested following a grid georeferenced in four seed production fields (1, 2, 3 and 4). It was determined the yield of each grid point and seeds physiological quality by germination, first count of germination, seedling emergence, massal and individual electrical conductivity. Spatial variability of physiological seed quality between fields was observed and also within each field, but with varying intensity. The massal and individual electrical conductivity, have proved accurate in the estimation of seed physiological quality, except of the field 3, as evidenced by the significant correlation with the germination and seedling emergence. The spatial variability of soybean seeds physiological quality can be estimated by the massal and individual electrical conductivity, mainly in high vigor seeds.